Evaluation of the use of bocashi in productivity and profitability in coffee cultivation - García Moreno, Alicia; Sánchez Lucio, Roberto; Reyes-Carrillo, José Luis; García Hernández, José Luis; Nava Camberos, Urbano; Cano Ríos, Pedro (Ecosistemas y Recursos Agropecuarios, 2025)
The demand for organic foods is increasing as consumers seek foods they consider healthier and safer. Consequently, various investigations have been conducted using different organic nutrition alternatives. The objective of this research was to evaluate the use of bocashi on productivity in coffee cultivation and to determine the profitability of this fertilizer when applied at different doses. The experiment was established on a plantation of standardized-sized native coffee trees, under regulated shade on land with a high diversity of trees, abundant foliage, good phytosanitary conditions, and an age of 25 years. The treatments evaluated were three doses of bocashi (three, six, and nine kg tree-1) plus an unfertilized control treatment, for a total of four treatments, with four replicates, each replicate on four trees. The treatments were evaluated using a randomized block design. The results showed significant differences in yield as the bocashi dose increased, reaching a difference of up to 0.47 t ha-1 compared to the control when 9 kg tree-1 was applied. In addition, the fruit length and width also improved significantly in each treatment. The economic analysis showed that only the 3 kg tree-1 dose is profitable when the coffee price is at least $19.14 per kg-1. The use of bocashi increased the yield and growth of coffee berries, but its profitability is affected by the price of the berries in each production cycle and the fertilizer doses.
Keywords: Fermented fertilizer; Coffea arabica; yield; organic production